Ceratozetidae (Acari: Oribatida) from lower Miocene mexican amber, including a new species of Trichoribates. (January 2023) - Ojeda, Margarita; Vega, Francisco J.; Rivas, Gerardo
Abstract: Trichoribates roynortoni Ojeda and Rivas sp. n. Is described based on one adult specimen preserved in estuarine stratified lower Miocene amber from the Campo La Granja mines, La Quinta Formation, Chiapas Mexico, which includes mostly estuarine aquatic and semiaquatic animals, but also an important amount of soil arthropods. This taxon is the first record for the Ceratozetidae family (Acari: Sarcoptiformes: Oribatida) and represents an addition to the few Acari reported for the Chiapas amber. Highlights: The first record of Ceratozetidae for Mexican amber is presented. A new species of Trichoribates Berlese, 1910) is described. Contributes to biodiversity of lower Miocene from Mexico.